Les sources de l’histoire du duché. Publications et inventaires récents - Pierre Bauduin (Tabularia)
Recent studies on the history of the duchy have largely drawn on the new light shed on sources available to scholars. The endeavours to publish the narrative texts have materialised not only intonew editions of the major works of the Norman chroniclers, but have also led to a rediscovery of the earliest Norman historiography and sustained debates concerning the processes of transmission of memory and the appropriation by a society of its past. The analysis of this production must take into consideration the other accounts of the history of theduchy. Although many acts remain unpublished, the corpus of diplomatic texts has grown and recent studies have inserted the Norman documentary evidence into the large debate on the "documentary transformation" which took place in the 11th century. Finally, the "underground archives", which were also resorted to, have drawn our attention to the importance of bringing together all the data provided by the texts and by archaeological evidence in order to seize the evolution of Norman society.